1998
DOI: 10.2307/3434317
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Biotransformation of Benzo(a)pyrene in an Isolated Perfused In Situ Catfish Intestinal Preparation

Abstract: In the aquatic environment, diet is an important route of exposure for the common contaminant and procarcinogen benzo(a)pyrene (BaP). Dietary organisms var'yin their BaP content and in contaminated areas often contain other xenobiotics including cytochrome P4501A inducers.This study eamined the effect of dose and previous dietary exposure to the inducer 3-naphthoflavone (BNF) upon the intestinal metabolism of BaP and the sptemic bioavailability of BaP-derived products in catfish. BaP was administered at 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…However, previous studies with fish have demonstrated the importance of extrahepatic metabolism. In vitro systems have been used to measure xenobiotic metabolism in both the gills [56] and gastrointestinal epithelium of fish [57,58]. Using an isolated perfused toadfish gut preparation, Van Veld [34] found that benzo[a]pyrene in the diet was extensively metabolized before entering the blood circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies with fish have demonstrated the importance of extrahepatic metabolism. In vitro systems have been used to measure xenobiotic metabolism in both the gills [56] and gastrointestinal epithelium of fish [57,58]. Using an isolated perfused toadfish gut preparation, Van Veld [34] found that benzo[a]pyrene in the diet was extensively metabolized before entering the blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the gastrointestinal tract of fish is metabolically active and that this metabolism can limit the bioavailability of compounds taken up from food [32][33][34]. This possibility was explored with the PBTK model by incorporating in vitro K M and V MAX values representative of liver tissue into mass balance equations for the gut tissue compartment.…”
Section: Modeling Approachmentioning
confidence: 99%
“…Poly(lactic‐coglycolicacid) (50–1000 nm, MW 40 000–75 000 g/mol) absorption in Caco‐2 cell lines was maximized for particles with diameters of about 100–200 nm and decreased for particles with diameters of 50, 500, and 1000 nm (Win and Feng 2005). In vitro human lung fibroblast uptake studies showed that processes on the surface of the cell were faster than the physical transport to the cell for substances ranging in hydrodynamic diameter from 25 to 500 nm (Limbach et al 2005). Aerosol NPs with median diameters of 22 nm are absorbed in rats via exposure to the lungs, and, after 1 h of exposure, 24% of the particles were located within and beyond the epithelial barrier (Geiser et al 2005).…”
Section: Pharmacological Studies and Nanoparticlesmentioning
confidence: 99%
“…BaP metabolites produced in the liver are secreted into the bile, concentrated and stored in the gallbladder before excretion into the intestine (Ferreira, Moradas-Ferreira, and Reis-Henriques 2006;Wang et al 2008;Zhu et al 2008). Although the liver is a major site of biotransformation of BaP, metabolism can also occur in extrahepatic tissues such as intestine, gills, and kidney (Costa et al 2011;James et al 1996;Kleinow et al 1998;Lemaire et al 1990). Reactive metabolites produced in these tissues can not only be transferred to the blood for elimination but can also be re-distributed to other organs, interfering with their functions and, as a consequence, producing toxicity.…”
Section: Introductionmentioning
confidence: 98%